Integration of Proteomics and Metabolomics Revealed Metabolite–Protein Networks in ACTH-Secreting Pituitary Adenoma - Feng, Jie; Zhang, Qi; Zhou, Yang; Yu, Shenyuan; Hong, Lichuan; Zhao, Sida; Yang, Jingjing; Wan, Hong; Xu, Guowang; Zhang, Yazhuo; Li, Chuzhong (Frontiers in Endocrinology, 2018)
Although surgery is a treatment option, an effective treatment with satisfying management of ACTH-PAs is currently lacking. We integrate the information obtained from the metabolomic and proteomic levels to identify critical networks and signaling pathways that may play important roles in metabolic regulation of ACTH-PAs and therefore hope to represent potential therapeutic targets. Six ACTH-PAs and seven normal pituitary glands was performed Gas chromatography-mass spectrometry (GC-MS) analysis for metabolomics. Fiv eACTH-PAs and five normal pituitary glands were used for proteomics analysis by nano liquid chromatography tandem-mass spectrometry (nanoLC-MS/MS). The joint pathway analysis and network analysis was performed by MetaboAnalyst 3.0 There were significant differences of metabolites and proteins in the expression between ACTH-PAs and normal pituitary glands. A proteomic analysis identified 417 differentially expressed proteins which were significantly enriched in Myc signaling pathway. Protein-metabolite joint pathway analysis showed differential expressed proteins and metabolites was significantly enriched Glycolysis/Gluconeogenesis, Pyruvate metabolism, Citrate cycle (TCA cycle) and Fatty acid metabolism pathway in ACTH-PAs. The protein-metabolite molecular interaction network from the metabolites and proteins identified from metabolomics and proteomics created four subnetworks. Ten nodes in subnetwork 1 were the most significantly enriched in cell amino acid metabolism and pyrimidine nucleotide metabolism. Additionally, Metabolite-Gene-Disease Interaction Network established nine subnetworks. Ninety-two nodes in subnetwork 1 were the most significantly enriched in carboxylic acid metabolism and organic acid metabolism. The present study clarified pathway networks that function in ACTH-PAs. Our results demonstrated downregulated glycolysis and fatty acid synthesis in this tumor. We also revealed that Myc signaling pathway significantly participated in metabolic change and tumorigenesis of ACTH-PAs. Those data may provide biomarkers for ACTH-PA diagnosis and monitoring, and also possibly lead to the development of novel strategies to treat pituitary adenomas.